2005
DOI: 10.1016/j.bbamem.2005.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer interaction and localization of cell penetrating peptides with model membranes: A comparative study of a human calcitonin (hCT)-derived peptide with pVEC and pAntp(43–58)

Abstract: Cell-penetrating peptides (CPPs) are able to translocate problematic therapeutic cargoes across cellular membranes. The exact mechanisms of translocation are still under investigation. However, evidence for endocytic uptake is increasing. We investigated the interactions of CPPs with phospholipid bilayers as first step of translocation. To this purpose, we employed four independent techniques, comprising (i) liposome buffer equilibrium dialysis, (ii) Trp fluorescence quenching, (iii) fluorescence polarization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 73 publications
3
13
0
Order By: Relevance
“…Apparently, the interaction of the peptide with neutral liposomes is weaker, when compared to the negatively charge membranes, and must be limited to the surface of the bilayer, making this interaction difficult to detect by other methods [21]. rBPI 21 interaction with pure POPC bilayers may be explained by the repulsion of the positive charged end group of the choline towards the aqueous phase, due to the high density of the positive amino acids in rBPI 21 , exposing the hydrophobic region of the lipid for the interaction with the peptide [38], [39]. Despite the lower aggregation state of the POPC∶LPS in the presence of rBPI 21 , the peptide is able to interact with negative charges of the LPS lipid A.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, the interaction of the peptide with neutral liposomes is weaker, when compared to the negatively charge membranes, and must be limited to the surface of the bilayer, making this interaction difficult to detect by other methods [21]. rBPI 21 interaction with pure POPC bilayers may be explained by the repulsion of the positive charged end group of the choline towards the aqueous phase, due to the high density of the positive amino acids in rBPI 21 , exposing the hydrophobic region of the lipid for the interaction with the peptide [38], [39]. Despite the lower aggregation state of the POPC∶LPS in the presence of rBPI 21 , the peptide is able to interact with negative charges of the LPS lipid A.…”
Section: Resultsmentioning
confidence: 99%
“…For several CPPs, binding, membrane insertion, bilayer disruption, translocation and/or fusogenicity have been characterized in such model systems. [30,32,33,[37][38][39] For example, some peptides derived from the HIV protein Tat (transacting activator of transcription) were shown to induce phospholipid mixing and vesicle fusion without detectable dye leakage, as seen by fluorescence. [32] Recently, it was also demonstrated that they can translocate through liposomes consisting of pure 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) [33] and through giant vesicles consisting of soybean phosphatidylcholine, but not through large unilamellar ones.…”
Section: Introductionmentioning
confidence: 97%
“…The mechanism of uptake of cationic CPPs is still unclear and some existing concepts, particularly the role of endocytosis in this process has been revised (40,42,70,71). Until recently, it was believed that internalization of CPPs involves the mechanism of endocytosis similar to the one described for bacterial and plant toxins that include their own transmembrane transfer apparatus (72).…”
Section: Mechanisms Of Membrane Translocation Of Cppsmentioning
confidence: 99%